STUDI DINAMIKA VEGETASI DI AREAL BEKAS PERLADANGAN DI DESA MANDOR KABUPATEN LANDAK Study the Dynamics of Vegetation in the Area Used for Cultivation in the Mandor Village Landak Distrik - Kustian, Reni; Budhi, Setia; Fernando, Togar (Universitas Tanjungpura, 2015)
Research goal is to investigate the dynamics of vegetation,Â composition and type of vegetation that grows naturally in the area used for cultivation in natural forest village where formerly the foreman that former shifting cultivation area has long been neglected and suffered natural regeneration. To determine the distribution and abundance of several types of vegetation used in the field by the method of vegetation analysis or transect lines by laying the first swath of purposive sampling (intentionally). In this study with the observation made 3 lanes each path length Â± 300 meters and a width of 20 meters. Distance between lines 100 meters, in one lane there were 15 plots observation that in one location observation plots contained 45 observations. So extensive observation location throughout the area used for cultivation is 1,8 Ha x 3 jalur = 5,4 Ha. Of the result of this study concluded to have formed the dinamics of vegetation in the area used for cultivation, this has caused the formation of patterns of diversity and structure of forest vegetation and forest vegetation that is already in a state of climax. Keywords : Dynamics, vegetation and used for cultivation